2008
DOI: 10.1051/dst:2007010
|View full text |Cite
|
Sign up to set email alerts
|

Volatile component change in whey protein concentrate during storage investigated by headspace solid-phase microextraction gas chromatography

Abstract: -Whey protein concentrate (WPC) is a nutritious ingredient and has gained popularity to be used in many traditional and novel food products. It typically has a shelf-life of 9 to 18 months when stored at room temperature. Fresh manufactured WPC could have a bland or slightly dairy, whey flavor. However, recognizable off-flavor can be developed during storage and this off-flavor becomes one of the major factors limiting its application in delicate formula. To understand the off-flavor development during the sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 18 publications
(28 reference statements)
4
26
0
1
Order By: Relevance
“…These results suggest that degradation has occurred in whey proteins, regardless of agglomeration treatment by this time. Javidipour and Qian (2008) found similar results during an accelerated storage study. Their research also showed that hexanal and heptanal concentrations initially increased in WPC80 followed by a subsequent decrease during storage.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…These results suggest that degradation has occurred in whey proteins, regardless of agglomeration treatment by this time. Javidipour and Qian (2008) found similar results during an accelerated storage study. Their research also showed that hexanal and heptanal concentrations initially increased in WPC80 followed by a subsequent decrease during storage.…”
Section: Resultssupporting
confidence: 69%
“…However, to our knowledge, few studies have addressed stability of WPC80 or WPI or the impact of agglomeration on the flavor and flavor stability of WPC80 and WPI. Javidipour and Qian (2008) evaluated instantized and noninstantized WPC80 from a single manufacturer under accelerated storage conditions and documented increases in relative abundance of selected volatile compounds including a range of aldehydes, suggestive of lipid oxidation. They observed that instantized product developed lipid oxidation products faster than noninstantized product.…”
Section: Introductionmentioning
confidence: 99%
“…The Flame Ionization Detector (FID) temperature was 270°C. All of the samples were analyzed in triplicate, and the same fiber was used for the entire experiment (Javidipour and Qian 2008). IS peak area ratio was used as an arbitrary unit for calculating the quantities of each volatile compound.…”
Section: Hs-spme-gc Analysismentioning
confidence: 99%
“…The instrument control and data analysis were performed using enhanced Chemstation software (Agilent Technologies, Inc., Santa Clara, CA, USA). Peak identification of volatiles was based on comparison of the MS spectra with the Wiley7n and Flavor2 libraries and with the spectra of injected standards as well as on the retention times of the standards (Javidipour and Qian 2008).…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…WPC powders that contain between 35% and 55% of proteins are mainly used in animal feed manufacture (Onwulata et al, 2003;Yun et al, 2005). Commercial WPC develops off flavor during storage and this problem is one of the major factor limiting its applications in delicate formula (Javidipour and Qian, 2008;Liaw et al, 2010). Two mechanisms (lipids oxidation and Maillard browning) are supposed to be the main causes of off flavor (Whitfield, 1992).…”
Section: Whey Protein Concentratesmentioning
confidence: 99%